Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
\(\sqrt{242}.\sqrt{26}.\sqrt{130}.\sqrt{0,9}-\left(\sqrt{2}-1\right)\left(\sqrt{2}+1\right)\)
\(=\sqrt{121}.\sqrt{2}.\sqrt{2}.\sqrt{13}.\sqrt{13}.\sqrt{10}.\sqrt{0,9}-\left(2-1\right)\)
\(=11.2.13.\sqrt{9}-1=286.3-1=857\)
\(\frac{3-\sqrt{6}}{\sqrt{12}-\sqrt{8}}-\frac{\sqrt{15}-\sqrt{5}}{2\sqrt{12}-4}+\frac{\sqrt{17-4\sqrt{15}}}{4}\)
\(=\frac{\sqrt{3}\left(\sqrt{3}-\sqrt{2}\right)}{2\left(\sqrt{3}-\sqrt{2}\right)}-\frac{\sqrt{5}\left(\sqrt{3}-1\right)}{4\left(\sqrt{3}-1\right)}+\frac{\sqrt{\left(2\sqrt{3}-\sqrt{5}\right)^2}}{4}\)
\(=\frac{\sqrt{3}}{2}-\frac{\sqrt{5}}{4}+\frac{2\sqrt{3}-\sqrt{5}}{4}\)
\(=\sqrt{3}-\frac{\sqrt{5}}{4}\)
![](https://rs.olm.vn/images/avt/0.png?1311)
\(1,\sqrt{\left(-0,3\right)^2}=\sqrt{0,09}=0,3\)
\(2,-\frac{1}{2}\sqrt{\left(0,3\right)^2}=-\frac{1}{2}.0,3=-0,15\)
\(3,\sqrt{a^{10}}=\sqrt{\left(a^5\right)^2}=a^5\left(a\ge0\right)\)
\(4,\sqrt{\left(2-x\right)^2}=\left|2-x\right|=2-x\left(x\le2\right)\)
\(5,\sqrt{x^2+2x+1}=\sqrt{\left(x+1\right)^2}=\left|x+1\right|\)
\(6,\sqrt{\left(1-\sqrt{2}\right)^2}=\left|1-\sqrt{2}\right|=\sqrt{2}-1\)(Vì \(1< \sqrt{2}\))
\(7,\sqrt{11+6\sqrt{2}}=\sqrt{9+6\sqrt{2}+2}=\sqrt{\left(3+\sqrt{2}\right)^2}=3+\sqrt{2}\)
\(8,\sqrt{8-2\sqrt{7}}-\sqrt{8+2\sqrt{7}}=\sqrt{7-2\sqrt{7}+1}-\sqrt{7+2\sqrt{7}+1}\)
\(=\sqrt{\left(\sqrt{7}-1\right)^2}-\sqrt{\left(\sqrt{7}+1\right)^2}\)
\(=\left(\sqrt{7}-1\right)-\left(\sqrt{7}+1\right)\)
\(=-2\)
\(9,\sqrt{6+2\sqrt{5}}+\sqrt{6-2\sqrt{5}}=\sqrt{5+2\sqrt{5}+1}+\sqrt{5-2\sqrt{5}+1}\)
\(=\sqrt{\left(\sqrt{5}+1\right)^2}+\sqrt{\left(\sqrt{5}-1\right)^2}\)
\(=\sqrt{5}+1+\sqrt{5}-1\)
\(=2\sqrt{5}\)
![](https://rs.olm.vn/images/avt/0.png?1311)
\(\sqrt{46-6\sqrt{5}}-\sqrt{29-12\sqrt{5}}\\ =\sqrt{\left(3\sqrt{5}\right)^2-2.3\sqrt{5}+1}-\sqrt{\left(2\sqrt{5}\right)^2-2.3.2\sqrt{5}+3^2}\\ =3\sqrt{5}-1-2\sqrt{5}+3=\sqrt{5}+2\)
Mấy câu sau tương tự.
![](https://rs.olm.vn/images/avt/0.png?1311)
a)\(\Leftrightarrow\)\(7\sqrt{x-2}-2\sqrt{x-2}-3\sqrt{x-2}=8\)
\(\Leftrightarrow\) \(3\sqrt{x-2}=8\)
\(\Leftrightarrow\) \(\sqrt{x-2}=24\)
\(\Leftrightarrow\)\(x-2=576\)\(\Leftrightarrow x=578\)
c)\(\Leftrightarrow GTTĐ\left(x-1\right)=\sqrt{2}-1\)\(TH1:x-1>0\)
\(\Rightarrow x-1=\sqrt{2}-1\)\(\Leftrightarrow x=\sqrt{2}\)
\(TH2:x-1< 0\)
\(\Rightarrow1-x=\sqrt{2}-1\)
\(\Leftrightarrow x=2+\sqrt{2}\)
d)\(TH1:x-10=0\Rightarrow x=10\)
\(TH2:\sqrt{x-4}=0\Rightarrow x=4\)
câu b) thì mik cần thêm time
\(\sqrt{\left(2\sqrt{2}-1\right)^2}-\sqrt{17+12\sqrt{2}}\)
\(\left|2\sqrt{2}-1\right|-\sqrt{17+6\sqrt{8}}\)
\(2\sqrt{2}-1-\sqrt{3^2+6\sqrt{8}+\sqrt{8}^2}\)
\(2\sqrt{2}-1-\left|3+\sqrt{8}\right|\)
\(2\sqrt{2}-1-3-\sqrt{8}\)
\(2\sqrt{2}-4-\sqrt{8}\)
\(=-4\)
\(\sqrt{x^2+x+4}=2\)
\(\left|x^2+x+4\right|=4\)
\(\orbr{\begin{cases}x^2+x+4=4\\x^2+x+4=-4\end{cases}}\)
ta có \(x^2+x+4=\left(x+1\right)^2+3>0\)
\(< =>x^2+x+4=-4\left(ktm\right)\)
\(x^2+x+4=4\)
\(x^2+x=0\)
\(x\left(x+1\right)=0\)
\(\orbr{\begin{cases}x=0\left(tm\right)\\x=-1\left(TM\right)\end{cases}}\)